Changing the Space in the Traditional Kerinci Traditional House - Fantoni (AKADEMI TEKNIK ADI KARYA, 2023)
This study aims to analyze changes in space in traditional Kerinci traditional houses. Research is research. In this case, the method used is a rationalistic method where this method seeks to explain the actual situation in the field and then tested with existing theories. The method chosen must be appropriate to achieve the research objectives, this chapter also examines in more detail about the research carried out such as research materials, research tools, the course of research, and difficulties encountered during research. The results of research findings that have been carried out on changes in the space in umah lahiek in Mukai Mukai Mudik Village, we can conclude that the changes that occur in the inner space are the addition of sleeping space both in the outer room (umah lua) and in the inner room (umah inside). The addition of this sleeping space has no effect on the shape of the outer floor plan of the umah lahiek unit, but only changes in the pattern of the inner room.